Brazilian consultants’ perception of the federal technical regulation of good practices for food services - Saccol, Ana Lúcia de Freitas; Viera, Fernanda Dineia; Giacomelli, Simone de Castro; Mumbach, Lidiane; Martello, Leonir; Hecktheuer, Luisa Helena Rychecki (Disciplinarum Scientia | Saúde, 2020)
The aim of this study was to evaluate the perception of aspects related to the Technical Regulation of Good Practices (GP) for Food Services by Brazilian consultants. An online questionnaire was distributed to all of the consultants registered in a national program for the implementation of quality management systems. A total of 131 consultants completed the survey. It was confirmed that only the state and the municipality of São Paulo have a Technical Regulation of GP within the ambit of Hospital Nutrition and Dietetics Services. Collegiate Board Resolution RDC No. 216/2004 was cited as the primary reference by the majority of the consultants. The lack of involvement of the employers in GP implementation and the difficulties with the food handlers were the main reported weaknesses. The criteria cited by practitioners included a lack of specifications and the reference to the binomial time/temperature. Given the subjects’ experience, another claim that should be considered was that the RDC No. 216/2004 is excessively broad and general. This perception indicates the need for supplementary health legislation by the state and municipal spheres, and also denotes that the federal legislation should be updated.